La justice des mineurs et The Boy’s Farm : 1909-1968 - Rains, Prue (Criminologie, 1985)
Reform schools for juvenile delinquents have shown remarkable resilience and adaptability in the face of changing public policy about how children who break the law should be treated. This paper is a case study of one Canadian reform school which has survived four serious population crises since 1909 : the Boy's Farm and Training School in Shawbridge, Quebec. In describing the first population crisis from 1921 to 1930, it focuses on the strategies adopted by the Boy's Farm's influential board of directors. In describing the three later population crises, it focuses on the struggle between the Boy's Farm and the Montreal Social Welfare Court over the commitment of older boys and emotionaly disturbed boys.